Sistem Rantai Pasok Dan Traceability Sayuran Hidroponik Di PT. Asabi - Riany, Matelda Septia; Fahmi, Idqan; Suprehatin, Suprehatin (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Supply chain and traceability are solutions for horticultural production, because supply chain can add value for product and traceability exists to ensure transparency, reduce the risks and costs. Asabi is one of the companies that runs horticultre business in Bogor with hydroponics systems. The presence of retail consumers needs higher quality, ensure integrity and safety. Therefore Asabi needs to implement a supply chain system and traceability for that consumer demand. This study uses primary data about business process, cycle time, and cost from observation and interviews with Asabi’s team. Secondary data: SCORmark by APICS and SCOR data by similar companies from internet and related research journal. Data were used to descriptive analysis using FSCN, calculating the SCOR, and analyzing the development of traceability. The data compare in two situations, before (H1) and after retail customers (H2). Asabi supply chain consists of upstream, processing and downstream. Supply chain SCOR performance shows that retail increases Asabi's sales, but lower reliability, and high cost. The traceability has not been built yet in Asabi, from the simulation application, Asabi needs to estimate the harvest, improve the sorting process and utilize the use of greenhouses to increase reliability and minimize costs.